Analisis Digital Marketing Untuk Menyusun Strategi Pemasaran Pada UMKM Restoran Tempat Bercakap Kopi di Kediri - Shofaa Muhayya; Achmad Zaini (Indo Publishing, 2026)
The development of digital marketing encourages Micro, Small, and Medium Enterprises (MSMEs) to utilize social media to improve competitiveness. However, Instagram has not been optimally utilized as a marketing medium by Tempat Bercakap Kopi Restaurant, Kediri. Therefore, analyzing digital marketing effectiveness is necessary to formulate appropriate marketing strategies. This study aimed to identify digital marketing activities through Instagram, analyze their effectiveness using Digital Marketing Metrics, and formulate marketing strategies. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, documentation, and Instagram Insights involving the Content Creator as the informant. Data were analyzed through data reduction, data presentation, and conclusion drawing, while digital marketing performance was evaluated using awareness, engagement, and conversion metrics. The results showed that Instagram was utilized as a marketing medium. Awareness reached new audiences, engagement reflected user interactions despite fluctuations, and conversion indicated Instagram was used for reservations. However, reservation records was systematically documented, limiting conversion evaluation. Based on these findings, marketing strategies included implementing a content calendar, optimizing content collaboration, improving customer interaction, and maintaining consistent visual design. This study concludes that Instagram marketing effectiveness requires further improvement, and the proposed strategies are expected to improve digital marketing performance.